2003
DOI: 10.3166/ijfp.6.53-70
|View full text |Cite
|
Sign up to set email alerts
|

Corner Deformation of Injected Thermoplastic Parts

Abstract: During the cooling process in injection molding, heat fluxes in the mold are generally lower in inner regious of corners. This asymmetric cooling generates a corner deformation: the part angle is smaller than the mold one. This phenomenon is known to be the main cause of corner warpage in injection molding of thermoplastics.The second phenomenon leading to a corner warpage has firstly been described for thin compression molded SMC parts and is called "spring forward effect". Due to the large fiberlength / part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Many studies have tested the deformation of unfilled thermoplastics. [14][15][16][17][18][19] Akay and Ozden 14 analyzed polycarbonate and acrylonitrile butadiene styrene and concluded that the examined specimens injection molded with a temperature difference between the two mold halves have resulted in the final part curving toward the hotter side of the mold. Tang et al 15 using acrylonitrile butadiene styrene plates for deformation analyses analyzed how melt temperature, filling time, packing pressure, and packing time affect warpage.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Many studies have tested the deformation of unfilled thermoplastics. [14][15][16][17][18][19] Akay and Ozden 14 analyzed polycarbonate and acrylonitrile butadiene styrene and concluded that the examined specimens injection molded with a temperature difference between the two mold halves have resulted in the final part curving toward the hotter side of the mold. Tang et al 15 using acrylonitrile butadiene styrene plates for deformation analyses analyzed how melt temperature, filling time, packing pressure, and packing time affect warpage.…”
Section: Introductionmentioning
confidence: 99%
“…Ammar et al 17 used a specimen with four corners (Figure 1(b)) for their warpage measurements. It was concluded that two phenomena caused the deformation of the part: the first was the asymmetrical cooling and the second was the spring forward effect.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation